Central Nervous System Involvement of Hemophagocytic Lymphohistiocytosis: When 18F-FDG PET/CT Solves a Complex Diagnostic Investigation. (October 2021) - Allard, Bastien; Delcroix, Olivier; Le Lez-Soquet, Servane; Sacaze, Elise; Querellou, Solène
Abstract : Abstract: Hemophagocytic lymphohistiocytosis is rare life-threatening syndrome, hereditary or acquired, mainly affecting children. Hemophagocytic lymphohistiocytosis is an immune deficiency characterized by severe inflammation caused by uncontrolled proliferation of activated lymphocytes and macrophages. The usual biological and clinical data may associate polyadenopathy, hepatosplenomegaly, fever, multivisceral damages, and cytopenias with potential multiorgan dysfunction and death. We report the case of a 4-year-old girl, hospitalized for recurrent cerebellar symptoms (ataxia) associated later with fever and pancytopenia. 18 F-FDG PET/CT revealed a node pathological uptake, which was biopsied and confirmed a diagnosis of hemophagocytic lymphohistiocytosis.